ANALYSIS OF KIDNEY FUNCTION PARAMETERS ON THE RENOPROTECTIVE EFFECTS OF ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH CHRONIC KIDNEY FAILURE - Mourisa, Cut; Sukatendel, Firya Nadine Chalishny (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
The renoprotective effect in chronic kidney disease (CKD) patients can be induced by antihypertensive therapy, which provides a vasodilatory effect on the blood vessels leading to the kidneys. This resulting renoprotective function is considered to slow the decrease in kidney function in CKD patients. The purpose of this study was to examine the effectiveness of antihypertensive therapy as renoprotective agents through the analysis of kidney function parameters in CKD patients. A descriptive design with a cross-sectional method was used, and the study sample used data from patient medical records, specifically focusing on kidney function parameters of CKD patients during the January-June 2023 treatment period at RSUD Sultan Abdul Aziz Syah Peureulak. Of the 134 respondents, there were two groups of patients receiving antihypertensive therapy: ACE-Inhibitors (ACEIs) and (angiotensin receptor blockers) ARBs. After conducting the Wilcoxon test, there were significant changes in kidney function parameters (Urea, creatinine, and eGFR) between before and after antihypertensive therapy, with a p value <0.05. In the ACEI group, the mean urea level was 72.4 ± 48.3 mg/dL, creatinine 4.8 ± 4.3 mg/dL, and eGFR 30.6 ± 30.8 mL/min. In the ARB group, mean urea was were 85.2 ± 48.7 mg/dL, creatinine 6.1 ± 4.2 mg/dL, and eGFR 21.6 ± 26.7 mL/min. These findings indicate that ACEI and ARB antihypertensive therapies are effective as renoprotective agents in CKD patients. Keywords: ACE-Inhibitor, antihypertensive, ARB, reno-protective effect DOI : 10.35990/mk.v8n4.p412-422